2014
DOI: 10.1002/rra.2801
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effects of Hydropeaking on Growth, Energetics and Movement of Juvenile Atlantic Salmon (Salmo Salar)

Abstract: The performance and movements of juvenile Atlantic salmon Salmo salar exposed to variable water discharge (simulating hydropeaking) but with a stable water‐covered area were studied in six experimental stream channels, both during the winter and summer. Thirty fish were stocked into each channel, and the growth, body fat and movements of the fish were followed for about 2.5 months in each season. During the winter, no effect of hydropeaking was documented on performance or movement. In the summer, fish experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 43 publications
(48 reference statements)
6
52
2
Order By: Relevance
“…The abiotic characteristics of the channels (depth, current, hydropeaking frequency and ramping speed) were identical to those of the previous study (Puffer et al 2014). The water temperature (mean temperature 13.2°C) decreased steadily during the experiment from 16.6 to 9.1°C.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…The abiotic characteristics of the channels (depth, current, hydropeaking frequency and ramping speed) were identical to those of the previous study (Puffer et al 2014). The water temperature (mean temperature 13.2°C) decreased steadily during the experiment from 16.6 to 9.1°C.…”
Section: Methodssupporting
confidence: 69%
“…The negative effects of hydropeaking are mainly associated with rapid changes in hydrology, the exposure of substrate and the stranding of fish and benthic invertebrates (Freeman et al 2001;Halleraker et al 2003;Korman & Campana 2009;Hauer et al 2014). Puffer et al (2014) performed experiments with juvenile Atlantic salmon Salmo salar in experimental flumes where stranding was avoided to investigate the effects of changing levels of discharge on fish performance. Furthermore, the effects of displacement may be sensitive to levels of intra-and interspecific competition, which may influence the cost of relocating to a suitable new patch.…”
Section: Introductionmentioning
confidence: 99%
“…Since body fat was the same for the control and treatment fish in all four experiments, stranding did not increase metabolism and thus did not influence winter survival in our experiments. In contrast to the present study, other studies [26] [38] showed that non-lethal effects of hydropeaking (i.e. changes in water discharge and water level without actual stranding) result in decreased growth and body fat in juvenile salmonids.…”
Section: Discussioncontrasting
confidence: 99%
“…The channels have been used in previously published experiments and are known to have an invertebrate fauna sufficient to feed small parr (e.g. [23] [24] [25]), but the experiments described below were designed to avoid abundance of food which may let the fish compensate negative growth effects of hydropeaking [26].…”
mentioning
confidence: 99%
“…Our results are based on 2-day fluctuations in water flow and suggest that salmonids may require time to adjust their behaviour (activity, mobility, and prey attack rates). For instance, Keenleyside and Yamamoto (1962) Earlier studies are equivocal on the effect of water flow fluctuations on growth, as some suggest that fish may grow slower (Flodmark et al, 2004;Puffer et al, 2015;Weyers, Jennings, & Freeman, 2003), faster (Finch, Pine, & Limburg, 2015), or at similar rate (Flodmark, Forseth, L'Abée-Lund, & Vøllestad, 2006;Korman & Campana, 2009;Puffer, Berg, Huusko, Vehanen, & Einum, 2017) in altered flow. Our results indicate that stream fishes compensate for low food intake under unfavourable conditions by adjusting their activity and foraging mode, that is, more activity and mobility under LWF, and the costs associated with such adjustments should be low.…”
Section: Discussionmentioning
confidence: 99%